INFORMATION-ALGORITHMIC SUPPORT FOR DEVELOPMENT OF SOLID PHARMACEUTICAL FORM - V. F. Kornushk (Тонкие химические технологии, 2018)
The article deals with the application of the system approach for constructing informationalgorithmic support for the pharmaceutical development of solid dosage forms. Information modeling of the life cycle of pharmaceutical drug development has been carried out starting from the stage of studying the active pharmaceutical substance and ending with the utilization of the drug. These models are built in the IDEF0 nomination. A generalized block diagram is presented that reflects, in its most general form, the iterative process of developing a ready-made dosage form as applied to the further transfer of technology. The basis of the system approach is QbD - "Quality planned in the development". To implement the QbD principle on the basis of the system approach, systemic set-theoretic models of information support of pharmaceutical development in the nomenclature of Melentiev have been constructed. A model for controlling the pressing process is also provided, which takes into account all the technological stages in the development of a solid dosage form. Functional models in the IDEF0 nomenclature of the technological process are constructed from the preparation of premises, personnel and components of the dosage form to the stage of packing and packaging of the finished dosage form. The construction of an informational intellectual control system for pharmaceutical development has been considered in detail with particular attention paid to the construction of a database of medicinal and auxiliary substances using the example of solid dosage forms. In Melentiev's bracket notation, the database of auxiliary substances necessary for the design of a solid dosage form is filled. The "Entity-relationship" model and the relational model for the database of medicinal and auxiliary substances have been constructe